Pengaruh Kompensasi terhadap Kinerja Pegawai di Dinas Pendidikan Daerah Provinsi Sulawesi Utara - Rafli Achmad; Joyce Jacinta Rares; Novva Novita Plangiten (Sam Ratulangi University, 2023)
ABSRACTThis study aims to examine the effect of compensation on employee performance at the Regional Education Office of North Sulawesi Province. The survey method is used to take samples from the population and collect data quantitatively. The data was processed from the results of distributing questionnaires to North Sulawesi Provincial Education Office employees with a total population of 155 people and a sample of 50 respondents. A basic linear regression analysis approach was applied in this investigation. The results of the study show that there is a positive influence between compensation and employee performance, so that the better the implementation of compensation, the better the employee performance.Keywords : Compensation, Employee, Performance ABSTRAKPenelitian ini bertujuan untuk mengkaji pengaruh kompensasi terhadap kinerja pegawai di Dinas Pendidikan Daerah Provinsi Sulawesi Utara. Metode survei digunakan untuk mengambil sampel dari populasi dan mengumpulkan data secara kuantitatif. Data diolah dari hasil penyebaran kuesioner kepada pegawai Dinas Pendidikan Provinsi Sulawesi Utara dengan jumlah populasi 155 orang dan sampel 50 responden. Pendekatan analisis regresi linier dasar diterapkan dalam penyelidikan ini. Hasil penelitian menunjukkan adanya pengaruh positif antara kompensasi dan kinerja pegawai, sehingga semakin baik penerapan kompensasi, semakin baik pula kinerja pegawai.Kata Kunci : Kompensasi, Pegawai, Kinerja